Toxic leadership and safety performance: Does organizational commitment act as stress moderator? - Farid Saleem; Muhammad Imran Malik; Muhammad Kamran Malik (Cogent Business & Management, 2021)
Ensuring safety is the key to sustainability especially, in the oil and gas sector. The study aims to examine the effects of five dimensions of toxic leadership on the safety performance of engineers working in Oil and Gas Companies. Through social learning theory and conservation of resource theory, an overarching framework of the research model has been proposed. Cross-sectional data from a sample of 219 site engineers, male and female, working in oil and gas companies operating in Pakistan, were collected and analyzed. Results revealed that out of five dimensions of toxic leadership, only abusive supervision and narcissism had a significant negative impact on safety performance. Similarly, organizational commitment appeared as an essential stress moderator and has successfully dampened the negative impact of abusive supervision and narcissism on safety performance.
Keywords: 650; Organizational commitment; safety performance; self-promotion; abusive supervision; unpredictability; narcissism; authoritarian leadership